PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK BERBASIS HIERARKI KONSEP POKOK BAHASAN HIDROLISIS GARAM - Yunika Devia; R. Usman Rery; Asmadi M. Noer; Oktafianus Oktafianus (Jurnal Pendidikan Kimia Universitas Riau, 2020)
This research is a research design to obtain a product prototype teaching material Student Activity Sheet (LKPD). LKPD to be designed and developed is the Concept Hierarchy Based LKPD for Salt Hydrolysis Subjects. The research method used was the research development of Sivasailam Thiagarajan et al. 4-D development model: Define, Design, Develop and Disseminate. Define stage/formulate student needs and synchronize the indicators/competencies that students want to achieve in understanding the HG material. The Design Stage is a designation of LKPD which has considered the inclusion of all BHK-based pursuit objective indicators contained in LKPD. The final result of the Design stage is the final draft of the LKPD (prototype) which must be validated which is carried out at the Develop stage. LKPD validation by three experts who assessed the feasibility aspects of content, linguistics, presentation and graphics, respectively scored 89.28%, 91.67%, 93.75% and 87.50% with valid categories. After LKPD was declared valid, LKPD was tested on high school students to see the responses and input from the teacher in the field of chemistry studies. Response of 20 students rated positive/useful with a score of 91.07% in the very positive category and assessed its practicality by two teachers and got the response results with a percentage of 93.75% with a very practical category.